A calixarene-based fluorescent ratiometric temperature probe. Issue 56 (24th June 2019) - Bardi, Brunella; Tosi, Irene; Faroldi, Federica; Baldini, Laura; Sansone, Francesco; Sissa, Cristina; Terenziani, Francesca
Abstract : We report the first macrocycle-based ratiometric molecular thermometer exploiting the conformational thermosensitivity of a calixarene functionalized with two different fluorophores. Abstract : We report the first macrocycle-based ratiometric molecular thermometer exploiting the conformational thermosensitivity of a calixarene functionalized with two different fluorophores. Thanks to the dependence on temperature of the efficiency of excitation energy transfer between the organic fluorophores, the thermometer works over a 60 °C-wide temperature range with a sensitivity of 4% °C −1 .